STRUCTURAL CHARACTERIZATION OF ALUMINOSILICATE CATALYST SUPPORTS SYNTHESIZED FROM LOCAL KAOLIN AND THEIR APPLICATION PROSPECTS IN PETROCHEMICAL PROCESSES - Khayrullo Shukrullo o‘g‘li Khotamov,Gozal Khusan qizi Yusupova (International Journal of Literature and Language Studies, 2026)
The efficiency of catalysts used in the petrochemical industry largely depends on the properties of their supports. Catalyst supports serve to uniformly disperse active components, enhance their mechanical strength, and increase the available reaction surface area. Therefore, the development of high-quality catalyst supports from inexpensive, environmentally friendly, and locally available raw materials is one of the pressing challenges in modern catalysis. Kaolin deposits located in Uzbekistan represent a promising source of raw materials for the production of aluminosilicate materials. In recent years, interest in the development of diesel distillate hydrotreating processes has increased significantly due to the growing volume of sulfur-containing and high-sulfur crude oil processing, as well as the widespread dieselization of transportation systems. It is well known that low-sulfur diesel fuels with improved performance characteristics are produced through the hydrotreatment of straight-run fractions and secondary feedstocks. Therefore, hydrotreating technologies have become one of the most important processes in modern petroleum refining, ensuring compliance with increasingly stringent environmental regulations and fuel quality standards.